The central bacterial community in Pericarpium Citri Reticulatae 'Chachiensis'. (November 2019) - He, Jing; Chen, Congcong; He, Qianxian; Li, Jingyu; Ying, Fan; Chen, Gu
Abstract: The dried and aged pericarps of Citri Reticulatae are condiments and medicinal products in southeast and eastern Asia for hundreds of years, among which Pericarpium Citri Reticulatae 'Chachiensis' (PCR-C) is the premium one with obvious health benefits. In order to explore the microbiota in PCR-C and their relationship with the chemical components during aging, culture-independent methods were applied to investigate PCR-C microbiota for the first time. Here in different PCR-C samples, 16S rRNA gene amplicon sequencing revealed common central bacterial community, which were absent or only accounted for small proportion in fresh pericarps or jute bag controls. Bacillus and Lactococcus were the top two dominant genera in PCR-C with acidic pH (4.06–4.51) and low moisture (11.48%–19.13%). Several OTUs were found to closely relate with specific compositions in essential oils and phenolics, such asd -limonene and nobiletin, which contributed to PCR-C flavor and quality. As the first study to reveal the central bacterial communities in PCR-C, it provides new insights to improve the quality and aging process of traditional Pericarpium Citri Reticulatae, and lays foundation for functional characterization of the microbes within. Graphical abstract: Unlabelled Image Highlights: Sequencing revealed common central bacterial community in different PCR-C samples. Bacillus and Lactococcus were the top two dominant genera in PCR-C. Several bacterial OTUs closely related with compositions in essential oil & phenolics.